2016
DOI: 10.1589/jpts.29.3095
|View full text |Cite
|
Sign up to set email alerts
|

Effects of body mass index on plantar pressure and balance

Abstract: [Purpose] To suggest physiotherapy programs and to determine foot stability based on the results of plantar pressure and spontaneity balance in the normal group and in the obesity group according to the body mass index (BMI). [Subjects and Methods] The plantar pressure and balance of 20 females college students in their 20s were measured according to their BMI. BMI was measured by using BMS 330. The peak plantar pressure was measured in a static position in the forefoot and hind-foot areas. To study balance, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 12 publications
1
5
1
2
Order By: Relevance
“…It was also found that there were varying correlations between the increase in total contact area and force parameters and the increase in weight and BMI, ranging from low to strong. Similar to our results, Yoon et al (10) found that there was no change in forefoot and hind-foot pressure in obese individuals. Birtane and Tuna (13) reported that total contact area and forefoot pressure values increased in obese individuals, but heel pressure was similar in obese individuals and individuals with normal weight.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…It was also found that there were varying correlations between the increase in total contact area and force parameters and the increase in weight and BMI, ranging from low to strong. Similar to our results, Yoon et al (10) found that there was no change in forefoot and hind-foot pressure in obese individuals. Birtane and Tuna (13) reported that total contact area and forefoot pressure values increased in obese individuals, but heel pressure was similar in obese individuals and individuals with normal weight.…”
Section: Discussionsupporting
confidence: 92%
“…In overweight/obese individuals, plantar pressure distribution in static posture in standing is the subject of very limited research (10)(11)(12)(13). Besides, the results of these studies are quite different.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bu nedenle, plantar basınç dağılımdaki değişiklikler alt ekstremite postüründe değişikliklere, ayak ve ayak ile ilişkili yapılarda anormal yüklenmelere neden olarak plantar fasiit ve ön diz ağrısı gibi ortopedik hastalıklara neden olabilir [5][6][7][8][9]. Ayakta statik duruş pozisyonunda plantar basınç dağılımının oldukça sınırlı araştırmaya konu olduğu görülmektedir [10][11][12][13]. Bununla birlikte bu çalışmaların sonuçları da oldukça farklılık göstermektedir.…”
unclassified
“…Örnek vermek gerekirse, bu çalışmaların bazılarında aşırı kilolu ve/veya obez bireylerde plantar basıncın arttığı bildirilirken [12,13], diğer çalışmalarda obez ve normal kilolu bireylerin plantar basınç dağılımının benzer olduğu bildirilmektedir [10,11]. Aşırı kilolu ve obez bireylerde plantar basınç dağılımındaki değişikliklerin ortaya konulması, bu bireylerde artmış alt ekstremite ve ayak ortopedik yaralanmaların daha iyi anlaşılmasını sağlayarak yeni koruyucu ve tedavi edici yaklaşımların geliştirilmesine yardımcı olabilir.…”
unclassified